PENGGUNAAN BUDIDAYA LORONG UNTUK REHABILITASI TANAH TEREROSI - W.H. Utomo; Titiek Islami (Universitas Tribhuwana Tunggadewi, 2006)
An experiment had been carried out to study the potential of alley cropping system for rehabilitation of eroded soil. The experiment was carried out on Vertisols at Ngrimbi, Jombang, East Java. The results showed that planting Gliricidia as an hedgerow crop in an alley cropping system improved the properties and fertility of eroded Vertisols. After 10 years of the practice, there was an increase in soil organic-C, soil N, Soil-P, and soil-K. As a result of increasing soil organic-C, there was an improvement of soil aggregation, water holding capacity, and available soil water. Improvement of soil fertility with alley cropping resulted in an increase of maize and soybean yields. The yields of maize and soybean in a non alley cropping system, on the other hand, constantly decreased with time